EVALUATION OF THE FREE RADICAL AND ANTIOXIDANT ABILITIES IN ETHANOLIC EXTRACT OF THE Breynia patens (Roxb.) Benth. & Hook. f. - K, MUTHURAJ; H, ABDUL KAFFOOR; N, NAGARAJAN (Asian Journal of Pharmaceutical and Clinical Research, 2015)
The present study evaluates the free radical and antioxidant abilities in the extract of Breynia patens. Some in vitro antioxidant assays were employed, Such as DPPH, ABTS, Reducing power assay, Ferrous ion chelating activity and Hydroxyl radical scavenging assays. The plant extract shows excellent activity in DPPH (IC50=43.47) and ABTS (6314.6Â±15.5 Âµmol/g). Reducing power assay indicates an increase in reductive ability, Ferrous ion chelating activity (IC50 = 303.03) and Hydroxyl radical scavenging assays (IC50=581.39). The results could be considered the plant as natural antioxidants and may be useful for curing diseases arising from oxidative deterioration and considered as a source of natural therapeutic agent.